Congenital genital tract obstruction as a challenge for functioning reproductive health: a study from a tertiary care center in Nepal - Katuwal, Neeta; Rana, Ashma (Nepal Journal of Obstetrics and Gynaecology, 2020)
Aims: To find out the uterovaginal anomalies associated with congenital genital tract obstruction and successes achieved in its management. Methods: This was a descriptive study done at department of Obs/Gyn at Tribhuvan University Teaching Hospital from April 2014 to April 2018. Types of genital tract obstruction, surgical treatment, success of management and surgical complications were studied. Results: Of 35 cases 16 (46%) consisted of adolescents aged 11-15 yrs. Majority cases of GTO was due to vaginal septum 12(34%): longitudinal 4(33%), mostly transverse vaginal septum (TVS) 8(67%): upper TVS 4 and lower TVS 4,one among each associated with concurrent Imperforate hymen (IH). Other GTO consisted of only IH cases 9 (26%), vaginal agenesis 7 (21%), non- communicating rudimentary horn 4 , non-communicating right cornua 1and cervical stenosis 1(3%). Resection of septum performed in 12 cases of vaginal septum. hymenectomy in 8 and rudimentary horn excision in 4 cases. Restenosis was common complication in six cases. Conclusions: Adolescent age of 11-15 years is the common age of presentation of genital tract anomaly with vaginal septum the most common. Pre-surgical assessment is the key to successful surgical outcome. Keywords: adolescent, congenital, genital tract obstruction, resection